Número: reflexões sobre as conceituações de Russell e Peano - Schön, Michaela Costa (2006)
This paper aimed the realization of a study concerning the philosophical epistemology of the concept of number, in which it still makes sense to ask: What is number? In this perspective, we have assumed as problematic the philosophical duality of the conceptualizations of numbers, according to Axiomatic (proposed by Peano) e by the Set Theory and Logics (proposed by Russell), being the Conceptualization of Number the problem of this research, concerning the possibility of introducing an ultimate definition to this concept. The focus of this research is in the polemics that exists about the number introduced by Russell (1872-1970) contrary to Piano s (1858-1932), taking as a basis Otte s criticism, introduced in the article: B. Russell Introduction to Mathematical Philosophy , 2001. The research was developed using, as a reference, the sense of Complementarity, as well as using proper qualitative methodological research procedures. As a conclusion, we are able to claim that numbers are: on one hand, characteristics of certain classes and, on the other hand, operative concepts. This way, the existence of polemics between philosophers like Frege and Russell, who have favored predicative aspects, that is, they define number in terms of cardinality and, others like Grassmann, Dedekind and Peano who have highlighted the ordinal numbers, justify Otto s proposition of complementarity between the approaches. The possibility of having cognitive and didactical consequences on the teaching in the use of one or another approach of conceptualization of the number or both, as Otte intends, makes this study a contribution to Mathematical Education